MODELING THE DIFFERENTIAL MOTION OF A MOBILE MANIPULATOR AND DESIGNING A NEW VISUAL SERVOING FOR TRACKING A FLYING TARGET - Thuong, Hoang Thi; Tinh, Nguyen Van; Kiem, Nguyen Tien (Journal of Computer Science and Cybernetics, 2018)
This article describes the process of modeling the differential motion of a mobile manipulator which is a two-degree-of-freedom robotic arm (pan-tilt) mounted on a wheeled mobile robot (WMR). Next, a new visual servoing is designed for this arm so that the image feature of a target converges to the center of the image plane of a camera which is attached to the arm’s end-effector, when not only the target considered as a material point is flying with an unknown trajectory but also the WMR is moving on the floor with another unknown trajectory. The global uniform asymptotic stability of this control method is guaranteed by Lyapunov standard. Simulation results implemented by Matlab-Simulink software confirm both the truth and performance of the entire system.